EULER-ZAGIER SUMS VIA TRIGONOMETRIC SERIES - Celik, Sermin Cam; Goral, Haydar (Editura Acad Romane, 2023)
In this note, we study the evaluations of Euler sums via trigonometric series. It is a commonly believed conjecture that for an even weight greater than seven, Euler sums cannot be evaluated in terms of the special values of the Riemann zeta function. For an even weight, we reduce the evaluations of Euler sums into the evaluations of double series and integrals of products of Clausen functions. We also re-evaluate Euler sums of odd weight using a new method based on trigonometric series.
Keywords: Euler Sums; Trigonometric Series; Values